Fundraising as an integration of creative non-commercial interests and private business opportunities - Igor M. Alikperov (Управление культурой)
Introduction. Fundraising activities have already become an integral part of social entrepreneurship, which uses both public resources and private capital. However, the crisis and unstable economic situation in the country makes it difficult for businesses to provide real assistance in the implementation of sociocultural projects, which requires the search for effective motivational mechanisms for business participation in the activities of non-profit creative organizations.In order to increase business motivation in financing non-profit creative organizations, these two entities should become partners, solving their own interests, at the same time creating interesting and important activities for their consumers, viewers. The purpose of the article is to identify marketing, fundraising tools for integrating the commercial opportunities of business structures with the public interests of non-profit creative organizations.The article discusses the issues of increasing the role of the creative economy in social development, the possible economic and social interests of business in financing creative projects of non-profit organizations through the search and work with a common target audience, from which four parties benefit - consumers, business, creative non-profit organizations and territories. Methodology. When writing the work, the following methods were used: comparative and logical analysis, generalization, observation, modeling. The results of the study show that due to the complication of the economic, political, international situation, and, accordingly, the deterioration of market conditions, the former forms of cooperation between non-profit creative organizations and business, in which the latter simply finances projects based on mentions in various documents, are no longer so effective and beneficial. A deeper integration of the interests of these two subjects is needed with the activation of sponsorship rights at the stage of identifying and establishing communications with a common target audience, and this is the establishment of partnerships based on strategic cooperation.Therefore, the value of such research is undoubted, especially since the practice of fundraising relations between business and non-profit creative organizations is far ahead of the level and volume of scientific analytics and developed recommendations for the successful development of both structures.